Lone Hepatocellular Carcinoma: An Isolated Chest Wall Malignancy - Joseph Allencherril; Sebastian Bruera; Ronan Allencherril; Richard J. Hamill (Case Reports in Medicine)
Herein we describe the case of an elderly diabetic gentleman presenting with a two-week history of dyspnea and nonproductive cough, found to have a large left anterolateral chest wall mass. Further characterization through computed tomography (CT) of the chest revealed a soft tissue mass in the left anterior lower hemithorax found to be hepatocellular carcinoma (HCC). The liver, spleen, and pancreas were unremarkable. Diagnostic labs were unremarkable. The patient had no history of hepatitis, alcohol abuse, or illicit substance use. Pathological examination and immunohistochemical staining of the chest mass biopsy were consistent with metastatic hepatocellular carcinoma (HCC). The patient opted to pursue no further medical intervention and expired two weeks later. To the authors’ knowledge, this is one of very few descriptions of isolated hepatocellular carcinoma found in the absence of a primary liver lesion and classical risk factors for hepatocarcinogenesis. This case highlights that HCC may present independently of liver lesions seen on imaging in a patient without clear signs or symptoms of liver. HCC should be considered in cases of isolated tumors with unclear primaries as ectopic carcinogenesis and occult primary malignancy are possibilities.